Pelatihan Pembuatan Noken dan Kiat Wirausaha Bagi Generasi Milenial Papua - Ngutra, Risky Novan; Febiana, Anggelika; Gobay, Helena Gracelia U.; Ilham, Ilham (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
The implementation of this activity is entitled Noken Making Training and Entrepreneurial Tips for Papuan Millennials. This activity was held in Koya Koso, Jayapura City. The implementation of the activity was carried out using lecture, training, and evaluation methods. The results of this activity show that participants during the training had very high enthusiasm to know the important role of understanding in preserving culture, especially noken making for the millennial generation. In making noken, almost all participants have learned to make noken, which at the beginning of the activity did not understand, after attending the training finally understood how to make noken. Meanwhile, in understanding what costs, income and profit are, which initially could not distinguish, finally after following the explanation during socialization, almost 90% of participants could understand it well. As a recommendation that can be conveyed in this Community Service activity, mothers and teenagers in Koya Koso should continue to train the existing generation in making traditional handicrafts in the form of woven noken as a characteristic of Papuans, and it is also hoped that the government, especially MSME actors, will always organize training activities for the community that can increase youth competence in managing business finances.